The effect of lactic acid fermentation on fig (Ficus carica) fruit flavonoid - Ernanin Dyah Wijayanti; Nur Candra Eka Setiawan (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2017)
Fig fruit contains a quite high flavonoid that supports the use of it for several disease therapies. Yet, most of the flavonoid in plants is difficult to be digested since it bounds with the glycoside, so the hydrolysis is necessary. The hydrolysis can be done through the lactic acid fermentation. This research aims to determine the effect of lactic acid fermentation on fig fruit flavonoid. Dried fig fruit was prepared into a fig fruit extract and fermented at 37°C for 24 hours using 4 types of starter bacteria; Lactobacillus acidophilus, L. bulgaricus, L. casei and L. plantarum. The fermentation result was identified its flavonoid using dye reaction, determined its flavonoid content using the spectrophotometry with the quercetin standard, and analyzed qualitatively using the LC-MS/MS. The results show that the flavonoid was identified in both before and after the fermentation, but the flavonoid content decreases 30 – 50% after the fermentation. The LC-MS/MS shows that the identified flavonoid is rutin, with the relatively higher percentage after the fermentation. In addition, the catechin and epicatechin are not detected. It can be concluded that the lactic acid fermentation affects the fig fruit flavonoid. The fermentation with all types of starter bacteria decreases the total flavonoid content of fig fruit juice.